Krisis Keuangan Global 2008-2009 dan Implikasinya pada Perekonomian Indonesia - Iman Sugema (Institut Pertanian Bogor, 2012)
The global financial crisis that occurred in 2008-2009 was the worst financial crisis in 80 years, even the economists in the world called it as the mother of all crises. The subprime mortgage crisis in the United States eventually manifested into a world-wide financial crisis. No single country is free from the effects, including Indonesia. This study aims to analyze the global financial crisis, the sources of the cause, the mechanisms of the crisis emergence, and to identify the implications of the crisis on financial sector and real sector, as well as employment and poverty. The results showed that the country has a relatively high poverty rate and unemployment rate than it should. If there is no crisis, the level of poverty alleviation and reduction of unemployment should be at a better rate. In addition, it was found that the impact of the global crisis relatively stronger to the rural households than to urban households. Therefore, because the rural labor market is much more flexible than that in urban areas, the impact of global crisis on rural unemployment rates is relatively weaker as well.